2018
DOI: 10.1039/c8ra06398b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a one-dimensional atomic crystal of vanadium selenide (V2Se9)

Abstract: The synthesis and nanoscale dispersion of a new one-dimensional (1D) material, V 2 Se 9 , in which chainshaped molecular units with strong covalent bonds are assembled in a crystal structure via weak van der Waals attraction between chains, were successfully carried out. V 2 Se 9 is synthesized by solid-state reaction and additional heat treatment. The synthesized V 2 Se 9 has excellent thermal stability up to 400 C and has been experimentally confirmed to be dispersed up to $20 nm or less through a specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…[14][15][16][17] Especially, 1D vdW materials possessing strong covalent intrachain bonds and weak interchain vdW interactions have the structural advantage of dangling bonds-free on their edges, which act as charge carrier scattering sites that deteriorate the transport property. [18][19][20][21] Moreover, it was theoretically confirmed that some of the 1D vdW materials exhibit thickness-dependent properties, such as the bandgap expansion with the indirect-to-direct transition as the number of unit chains decrease from their bulk crystal, similar to well-studied transition metal dichalcogenides (TMDs). [22][23][24][25] Based on this aspect, numerous studies have been conducted to utilize 1D nanowires in functional electronic devices such as FET [26][27][28][29] and photodetectors, [30][31][32][33] but diversity among promising materials is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Especially, 1D vdW materials possessing strong covalent intrachain bonds and weak interchain vdW interactions have the structural advantage of dangling bonds-free on their edges, which act as charge carrier scattering sites that deteriorate the transport property. [18][19][20][21] Moreover, it was theoretically confirmed that some of the 1D vdW materials exhibit thickness-dependent properties, such as the bandgap expansion with the indirect-to-direct transition as the number of unit chains decrease from their bulk crystal, similar to well-studied transition metal dichalcogenides (TMDs). [22][23][24][25] Based on this aspect, numerous studies have been conducted to utilize 1D nanowires in functional electronic devices such as FET [26][27][28][29] and photodetectors, [30][31][32][33] but diversity among promising materials is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new types of inorganic molecular wires (IMWs), such as Mo 3 Se 3 – , Mo 6 S 3 I 6 , Nb 2 Se 9 , and V 2 Se 9 IMWs, have been investigated. These IMWs are obtained from bulk inorganic materials, in which individual IMWs are stacked together via weak van der Waals forces or ionic attractions. The isolated IMWs have a diameter of ∼1 nm, and their physical characteristics, such as their dimension, flexibility, and surface charge, are similar to those of components of the native ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their structural characteristics, weak van der Waals (vdWs) interaction between layers, 2D materials could be exfoliated as atomically thin layers with chemical and physical exfoliation methods; thus, various research topics related to the physical phenomena of atomic-scale materials have been expanded. Recently, studies on one-dimensional (1D) unit chain materials have been actively conducted with a concept similar to these 2D layered materials. Unlike 2D materials, 1D materials maintain strong covalent bonds in the unit chain direction, but through weak vdWs bonds between chains, it has the advantage of ultimately being able to be exfoliated into 1 nm-sized chains without dangling bonds. The dangling bonds are scattering centers on the edge of 2D materials and degrade the carrier-transport properties . From the absence of dangling bonds, Q1D and 1D materials can maintain superior properties when they go to the nanoscale.…”
Section: Introductionmentioning
confidence: 99%